A signiﬁcant decrease of the fundamental Schumann resonance frequency during the solar cycle minimum of 2008-9 as observed at Modra Observatory - ONDRÁŠKOVÁ, Adriena; ŠEVČÍK, Sebastián; KOSTECKÝ, Pavel (Contributions to Geophysics and Geodesy, 2009)
The Schumann resonances (SR) are electromagnetic eigenmodes of the resonator bounded by the Earth’s surface and the lower ionosphere. The SR frequency variability has been studied for more than 4 decades. Using data from the period 1988 to 2002, S´atori et al. (2005) showed that the SR fundamental mode frequency decreased on the 11-year time scale by 0.07 – 0.2 Hz, depending on which component of the ﬁeld was used for estimation and likely also on the location of the observer. A decrease by 0.30 Hz from the latest solar cycle maximum to the minimum of 2009 is found in data from Modra Observatory. This extraordinary fall of the fundamental mode frequency can be attributed to the unprecedented drop in the ionizing radiation in X-ray frequency band. Although the patterns of the daily and seasonal variations remain the same in the solar cycle minimum as in the solar cycle maximum, they are signiﬁcantly shifted to lower frequencies during the minimum. Analysis of the daily frequency range suggests that the main thunderstorm regions during the north hemisphere summer are smaller in the solar cycle minimum than in the maximum.